Development of a Mathematics Spinning Wheel for Teaching Arithmetic in Grade II Elementary School: Mathematics Spinning Wheel for Grade II Arithmetic - Fadhia Nabila; Widia Agustin; Elyana Elyana; Taufik Ilham (Primary Education Insight, 2025)
This study aims to develop and evaluate the Mathematics Spinning Wheel as an instructional medium to enhance the learning outcomes of second-grade elementary school students in arithmetic operations, specifically addition and subtraction. Employing a research and development (R&D) methodology, the study adopts the ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation. The research participants comprised 28 second-grade students from SD Negeri 211 Palembang. Data collection instruments included observations, interviews, validation questionnaires completed by subject matter and media experts, practicality questionnaires from teachers and students, and learning outcome tests. Validation results indicated a very high level of feasibility, with an average score of 82.69%. Practicality assessments showed the media was rated as highly practical, receiving scores of 90.4% from students and 91.3% from teachers. Effectiveness testing revealed a significant improvement in students’ average scores, from 64.04 in the pre-test to 79.25 in the post-test, with classical completeness increasing from 28.57% to 85.71%. These findings demonstrate that the Mathematics Spinning Wheel is a valid, practical, and effective instructional medium. It offers a fun and interactive alternative for mathematics learning and holds potential for further development across different topics and educational levels.